Distribution and risk factors for Plasmodium and helminth co-infections: a cross-sectional survey among children in Bagamoyo district, coastal region of Tanzania. - Nahya Salim; Stefanie Knopp; Omar Lweno; Ummi Abdul; Ali Mohamed; Tobias Schindler; Julian Rothen; John Masimba; Denis Kwaba; Alisa S Mohammed; Fabrice Althaus; Salim Abdulla; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Plasmodium and soil transmitted helminth infections (STH) are a major public health problem, particularly among children. There are conflicting findings on potential association between these two parasites. This study investigated the Plasmodium and helminth co-infections among children aged 2 months to 9 years living in Bagamoyo district, coastal region of Tanzania. METHODS:A community-based cross-sectional survey was conducted among 1033 children. Stool, urine and blood samples were examined using a broad set of quality controlled diagnostic methods for common STH (Ascaris lumbricoides, hookworm, Strongyloides stercoralis, Enterobius vermicularis, Trichuris trichura), schistosoma species and Wuchereria bancrofti. Blood slides and malaria rapid diagnostic tests (mRDTs) were utilized for Plasmodium diagnosis. RESULTS:Out of 992 children analyzed, the prevalence of Plasmodium infection was 13% (130/992), helminth 28.5% (283/992); 5% (50/992) had co-infection with Plasmodium and helminth. The prevalence rate of Plasmodium, specific STH and co-infections increased significantly with age (p < 0.001), with older children mostly affected except for S. stercoralis monoinfection and co-infections. Spatial variations of co-infection prevalence were observed between and within villages. There was a trend for STH infections to be associated with Plasmodium infection [OR adjusted for age group 1.4, 95% CI (1.0-2.1)], which was more marked for S. stercoralis (OR = 2.2, 95% CI (1.1-4.3). Age and not schooling were risk factors for Plasmodium and STH co-infection. CONCLUSION:The findings suggest that STH and Plasmodium infections tend to occur in the same children, with increasing prevalence of co-infection with age. This calls for an integrated approach such as using mass chemotherapy with dual effect (e.g., ivermectin) coupled with improved housing, sanitation and hygiene for the control of both parasitic infections.